The increasing use of the WHO Safe Childbirth Checklist: lessons learned at the Yaoundé Gynaeco-Obstetric and Paediatric Hospital, Cameroon - Julius Sama Dohbit; Namanou Ines Emma Woks; Carlin Héméry Koudjine; Willy Tafen; Pascal Foumane; Assumpta Lucienne Bella; Rosemary Nkemdilim Ogu; Fru Fobuzshi Angwafo (BMC, 2021)
Abstract Background Safe childbirth remains a daunting challenge, particularly in low-middle income countries, where most pregnancy-related deaths occur. Cameroon's maternal mortality rate, estimated at 529 per 100,000 live births in 2017, is significantly high. The WHO Safe Childbirth Checklist (SCC) was designed to improve the quality of care provided to pregnant women during childbirth. The SCC was implemented at the Yaoundé Gynaeco-Obstetric and Paediatric Hospital to improve the quality of care during childbirth. Methods This study was a retrospective study to determine the adoption rate of the SCC and its association with maternal (eclampsia, perineal tears, and postpartum haemorrhage) and neonatal (stillbirth, neonatal asphyxia and neonatal death) complications. Data were collected 6 months after the introduction of the SCC. Multivariate binary logistic regression was used to analyse the association between the use of the SCC and maternofoetal complications. Results Out of 1611 deliveries conducted, 1001 records were found, giving a retrieval rate of 62%. Twenty-five records were excluded. During the study period, the checklists were used in 828 of 976 clinical notes, with an adoption rate of 84.8% and a utilization rate of 93.9% at 6 months. Severe preeclampsia/eclampsia was associated with the non-use of the SCC (2.1 vs 5.4%, p = 0.041). Stillbirth, neonatal asphyxia, and neonatal death rates were not significantly different between the checklist and non-checklist groups. However, for all neonatal outcomes, the proportion of complications was lower when the checklist was used. Conclusion The use of the SCC was associated with significantly reduced pregnancy complications, especially for reducing the rates of severe pre-eclampsia/eclampsia. The use of the SCC increased to 93.9% of all deliveries within 6 months. We advocate for the use of the WHO Safe Childbirth Checklist in maternity units.